Language Variation in Minang Colloquial Language Spoken in Kabun region: Sociolinguistic Study on Millennial Citizens - Condra Antoni; Irham Irham; Gusna Ronsi (Masyarakat Linguistik Indonesia Universitas Andalas, 2019)
Despite the endless discussion on standard and non-standard language, Minangkabau and its dialect have less attention from scholars to study. This paper, therefore, aims to elaborate and compare the variation of Minang colloquial language and Sijunjung dialect spoken in Kabun region. Sociolinguistic theory on language variation and contact were employed to reveal such differences. In terms of data collection, we make use of Buffalo Trophy